Foundations of Afrocentric thought and practice and its implications as an alternative educational philosophy for African American individual and community empowerment. - Ashanti-alexander, Raushan Paul. (My University, 1999)
Afrocentricism stems from a total attempt by African Americans to define themselves based on their own value system and their interpretation of reality in which they find themselves without Eurocentric interference, domination or control. As an educational model, Afrocentricism is suggested as a means to solve the social, cultural educational and economic malaise that is presently afflicting the American community. The validity of the Afrocentric paradigm is supported by archeological, anthropological, historical, and educational data gathered by scholars intent upon providing an educational alternative for African children. Their research challenges traditional Eurocentric educational thought and practice that Afrocentric proponents believe limit, restrict, ignore and or prohibit the inclusion of other people's experience into the educational canon.

Although considered to be a "new" educational movement, historical analysis has shown that the Afrocentric thrust in education promoted during the 1970's and 80's is not a recent phenomenon. On the contrary, it has been a means of protest against Eurocentric racial discrimination and oppression since the 14th century. Afrocentricism is grounded in the social, political, cultural and educational experiences of the African. American community.
Keywords: History, Black.; African Americans Study and teaching Philosophy.; Education, Philosophy of.; African Americans Study and teaching Methodology.; Education, Curriculum and Instruction.; Education, History of.; Afrocentrism.